งูเห่า: ภาพสะท้อนวัฒนธรรมการเมืองของไทยหลังเลือกตั้ง 24 มีนาคม 2562 - พิมพ์พันธ์, วิระยา; พิมพ์พันธ์, สุชาติ (วารสารศรีล้านช้างปริทรรศน์; Vol 6 No 2 (2020): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 6 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2563), 2020)
คำว่า “งูเห่า” เป็นคำเปรียบเปรยนักการเมืองที่แปรพักตร์ไปอยู่พรรคอื่น มีพฤติกรรมทำร้ายต้นสังกัดหรือทำลายความไว้วางใจของประชาชนด้วยการเลือกเข้าไปอยู่กับพรรคการเมืองที่มีอุดมการณ์แตกต่างจากที่ต้นเคยยึดถือไว้ สาระที่จะนำเสนอในบทความนี้เป็นการสะท้อนวัฒนธรรมการเมืองของไทยหลังการเลือกตั้ง  และวิเคราะห์เหตุการณ์ที่นายสมัคร สุนทรเวช ขณะที่เป็นหัวหน้าพรรคประชากรไทย ใช้คำนี้เรียก ส.ส. พรรคประชากรไทย กลุ่มของนายวัฒนา อัศวเหม จำนวน 13 คน ที่แปรพักตร์ไปสนับสนุนนายชวน หลีกภัย เป็นนายกรัฐมนตรี ส่วนมติพรรคร่วมรัฐบาลเดิมที่จะสนับสนุนให้ พลเอก ชาติชาย ชุณหะวัณ ขึ้นดำรงตำแหน่งนายกรัฐมนตรี ภายหลังจากพลเอก ชวลิต ยงใจยุทธ ได้ลาออกจากการเป็นนายกรัฐมนตรีเนื่องจากประสบปัญหาเกี่ยวกับการแก้ไขปัญหาเศรษฐกิจ ในปี พ.ศ. 2541 เปรียบเหมือนพฤติกรรมของงูเห่าในนิทานอีสปเรื่องชาวนากับงูเห่า ซึ่งเป็นพฤติกรรมที่สร้างความเสียหายร้ายแรงต่อระบอบประชาธิปไตยและต่อบรรทัดฐานทางด้านคุณธรรมและจริยธรรมของนักการเมือง หากพฤติกรรมที่เกิดขึ้นนั้นอยู่บนพื้นฐานของการไม่มีจุดยืนทางอุดมการณ์การเมือง เป็นนักแสวงหาผลประโยชน์จากอำนาจการเมือง และเป็นนักฉวยโอกาสทางการเมืองเพื่อหวังผลประโยชน์และอำนาจเฉพาะตนเอง The term "cobra" was a metaphor for politicians who deviated from other parties. It was used to call any politician who acted as a viper or a poisonous snake in Aesop’s Fables. It was referred to the behavior of attacking one’s agency or destroying the trust of the people by choosing to live with a political party with a different ideology. The subject matter presented in this article is a reflection on Thai political culture after the election and analyzing the political events when Mr. Samak Sundaravej, the leader of the Thai Population Party, calling the Thai Democrat Party MP, a group of 13 led by Mr. Watana Asawahem who conversed to support Mr. Chuan Leekpai, the Prime Minister. At that time, the resolution of the former coalition government would support General Chatichai Choonhavan as Prime Minister after General Chavalit Yongchaiyudh resigned as prime minister due to experiencing economic problems in 1998. This is like the behavior of a cobra in Aesop's Fables, the farmer and the cobra, which causes serious damage to democracy and the moral and ethical norms of politicians. If the behavior is based on the lack of political ideology, the politicians become persons who seek benefits from political power and being a political opportunist, striving for his interests and power.